Politics and power in the courts of two queens: cleopatra of Egypt and India of the old Benin kingdom (2016)
The aim of this paper is to examine the character, personality, intrigues involved in the power and politics o f two different female principalities who existed and reigned in tM’o distinct epochs. Queen Cleopatra o f Egypt exhibited skills which surpassed those o f her predecessors and secured her position as Pharaoh in Egypt. Queen Idia of the old Benin Kingdom was a powerful political figure who, during her incumbency, sustained her son, Oba Esigie on the throne. The paper contends that both female leaders believed in their capacity to rule, therefore, they exuded strong political strategies for the greater good o f their interest. This paper discovers that both queens who were indeed brave utilized what they possessed to achieve what they desired. Consequently, Queen Cleopatra won the support and love o f Julius Caesar first and then Mark Anthony. The title of Jyioba, (King’s mother) was bestowed on Queen Idia by her son the Oba (king) o f Benin. Studies that may interrogate political strategies o f some leaders in both ancient Rome and Benin Empire are recommended.